2003
DOI: 10.1375/bech.20.2.94.24837
|View full text |Cite
|
Sign up to set email alerts
|

Fears and Fearfulness in South-African Children

Abstract: The present study examined common childhood fears in 9-to 13-year-old South-African children (N = 404) from white, coloured, and black cultural groups. Fears were assessed by means of two methods -the fear list method and the Fear Survey Schedule for Children-Revised (FSSC-R). Results showed that fear rank orders as obtained with the fear list method were quite different from those derived from the FSSC-R. Furthermore, clear differences in fear levels were found among the three cultural groups. More specifical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
1
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 35 publications
(41 reference statements)
4
20
1
2
Order By: Relevance
“…Burkhardt et al, 2003;Muris et al, 2002], our data showed no significant differences on MASC total and most subscale scores. Two exceptions, however, were the Harm Avoidance and Separation/Panic subscales.…”
Section: Discussioncontrasting
confidence: 64%
“…Burkhardt et al, 2003;Muris et al, 2002], our data showed no significant differences on MASC total and most subscale scores. Two exceptions, however, were the Harm Avoidance and Separation/Panic subscales.…”
Section: Discussioncontrasting
confidence: 64%
“…Ingman et al (1999), also using the FSSC-R, compared children and adolescents from Kenya and Nigeria (and also to other countries tested in previous studies), and found that Nigerian children reported higher levels of fear than Kenyan children, while children from both countries scored higher than UK, US, Australian and Chinese children. Burkhardt et al (2003), again using the FSSC-R as well as the Fear List Method to compare White, Colored, and Black children in South Africa, reported that results of the two instruments were not identical, but also not contradictory. On the Fear List Method, Black and Colored children reported a higher number of fears which they classified as serious compared to White children.…”
Section: Challenging Conventional Wisdommentioning
confidence: 99%
“…In eigen onderzoek naar de angstniveaus van kinderen in Zuid-Afrika, werd consistent gevonden dat zwarte en gekleurde kinderen in Zuid-Afrika beduidend angstiger zijn dan de blanke kinderen in dit land (Burkhardt, Loxton, & Muris, 2003;Muris, Loxton, Neumann, & Du Plessis, in druk;Muris, Schmidt, Engelbrecht, & Perold, 2002). Deze verschillen werden vrijwel uitsluitend verklaard door de sociaal-economische omstandigheden waarin de kinderen opgroeien.…”
Section: Samenleving En Cultureel Bepaalde Idealenunclassified